Identification of a Short Cell-Penetrating Peptide from Bovine Lactoferricin for Intracellular Delivery of DNA in Human A549 Cells - Liu, Betty R.; Huang, Yue-Wern; Aronstam, Robert S.; Lee, Han-Jung (PLOS ONE, 2016)
Cell-penetrating peptides (CPPs) have been shown to deliver cargos, including protein, DNA, RNA, and nanomaterials, in fully active forms into live cells. Most of the CPP sequences in use today are based on non-native proteins that may be immunogenic. Here we demonstrate that the L5a CPP (RRWQW) from bovine lactoferricin (LFcin), stably and noncovalently complexed with plasmid DNA and prepared at an optimal nitrogen/phosphate ratio of 12, is able to efficiently enter into human lung cancer A549 cells. The L5a CPP delivered a plasmid containing the enhanced green fluorescent protein (EGFP) coding sequence that was subsequently expressed in cells, as revealed by real-time PCR and fluorescent microscopy at the mRNA and protein levels, respectively. Treatment with calcium chloride increased the level of gene expression, without affecting CPP-mediated transfection efficiency. Zeta-potential analysis revealed that positively electrostatic interactions of CPP/DNA complexes correlated with CPP-mediated transport. The L5a and L5a/DNA complexes were not cytotoxic. This biomimetic LFcin L5a represents one of the shortest effective CPPs and could be a promising lead peptide with less immunogenic for DNA delivery in gene therapy.